The Effect of Segmenting and Contiguity Principles on Students’ Cognitive Load in Science Learning - Aisyah Ary Yatma; Ismail Fikri Natadiwijaya; Putri Anjarsari (CV. Edujavare Publishing, 2025)
Science learning requires students to understand concepts deeply; however, the complexity of the material and the dense and poorly structured presentation of information often increase students’ cognitive load. This study aims to examine the effect of segmenting and contiguity principles on students’ cognitive load in science learning. A quasi-experimental method with a posttest-only control group design was employed. The participants were eighth-grade students of MTs Negeri 9 Bantul, divided into an experimental group and a control group. The experimental group was taught using learning activities based on segmenting and contiguity principles, while the control group received regular instruction. Students’ cognitive load, particularly intrinsic and extraneous cognitive load, was measured using the Paas Mental Effort Rating Scale. The data were analyzed using descriptive statistics, independent samples t-test, and effect size. The results revealed that the application of segmenting and contiguity principles had a significant and moderate effect on reducing students’ cognitive load compared to conventional science learning (p = 0.016; Cohen’s d = 0.633). These findings indicate that instructional designs applying segmenting and contiguity principles are effective in managing students’ cognitive load and supporting more meaningful and cognitively efficient science learning.